On free time optimal control - Maria do Rosário de Pinho (2010)
Here we consider free time optimal control problemsinvolving mixed state-control constraints. For suchproblems we derive necessary conditions of optimality in theform of a Maximum Principle appealing to recent results onmixed constraints where necessary conditions in the form ofa nonsmooth maximum principles are derived under minimalregularity assumptions. Applications to optimal controlproblems involving differential algebraic equations are alsoconsidered.